Comparison of transcriptional profiles of Clostridium thermocellum grown on cellobiose and pretreated yellow poplar using RNA-Seq - Wei, Hui; Fu, Yan; Magnusson, Lauren; Baker, John O.; Maness, Pin-Ching; Xu, Qi; Yang, Shihui; Bowersox, Andrew; Bogorad, Igor; Wang, Wei; Tucker, Melvin P.; Himmel, Michael E.; et al. (Frontiers in Microbiology, 2014)
The anaerobic, thermophilic bacterium, Clostridium thermocellum, secretes multi-protein enzyme complexes, termed cellulosomes, which synergistically interact with the microbial cell surface and efficiently disassemble plant cell wall biomass. C. thermocellum has also been considered a potential consolidated bioprocessing (CBP) organism due to its ability to produce the biofuel products, hydrogen and ethanol. We found that C. thermocellum fermentation of pretreated yellow poplar (PYP) produced 30% and 39% of ethanol and hydrogen product concentrations, respectively, compared to fermentation of cellobiose. RNA-seq was used to analyze the transcriptional profiles of these cells. The PYP-grown cells taken for analysis at the late stationary phase showed 1211 genes up-regulated and 314 down-regulated by more than 2-fold compared to the cellobiose-grown cells. These affected genes cover a broad spectrum of specific functional categories. The transcriptional analysis was further validated by sub-proteomics data taken from the literature; as well as by quantitative reverse transcription-PCR (qRT-PCR) analyses of selected genes. Specifically, 47 cellulosomal protein-encoding genes, genes for 4 pairs of SigI-RsgI for polysaccharide sensing, 7 cellodextrin ABC transporter genes, and a set of NAD(P)H hydogenase and alcohol dehydrogenase genes were up-regulated for cells growing on PYP compared to cellobiose. These genes could be potential candidates for future studies aimed at gaining insight into the regulatory mechanism of this organism as well as for improvement of C. thermocellum in its role as a CBP organism.